REFLEKSI DIRI SEBAGAI INSPIRASI KARYA LUKIS - Ibnu Madjid, bandung (Arty: Jurnal Seni Rupa, 2015)
The study project entitled " Self Reflection in the Art of Painting " . Self-reflection becomes the most attached to the writer's life just before the deadline for the lecture . The idea gained after a very long reflection . The purpose of this study the authors chose the project is to reflect the author's personal life experiences into works of art with a realistic style featuring a portrait of the author and his facial expression. Works of art will not be created without the media in the form of materials , tools and techniques. Media used by the author is oil paint with a brand Rembrant , Amsterdam and Maries on canvas . The canvas used is varied sizes . Methods of work of art through the realization of ideas directly on canvas until the finishing continued with the presentation of works of art . Works of art made ​​with a realistic approach. Overall ten paintings produced writers , representing about the author's personal life experiences during their period of study. Subjects were shown was the subject of a portrait of the author 's face. By author of ten , four paper measuring 90 x 70 cm of which , entitled Artist Wanna Be , Counter Pleasure , Death Line . Two works measuring 60 x 60 cm which Player and Sing a Song . The work titled Keep Silent with a size of 50 x 50 cm , Blind measuring 70 x 50 cm , Work Hard measuring 100 x 80 cm , Muse size of 70 x 50 cm , and Many Hope measuring 80 x 100 cm. Given that the author made a study project is expected to contribute significantly to the Unnes academics in the field of painting in particular. For students , especially students of art both non education or even education , it is expected the author to be more creative in the work and further explore ideas and media in the work of art .